Using developmental evaluation principles to build capacity for knowledge mobilisation in health and social care. (July 2019) - Harper, Lesley M.; Dickson, Rumona
This article contributes to Developmental Evaluation practice by highlighting the impact of embedding Developmental Evaluation principles into the learning approach of a capacity building initiative named Evidence for Change. The health and social care teams participating in Evidence for Change were operating within a complex environment requiring radical change to tackle health inequalities and provide modern, cost-effective, evidence-informed, quality of care for all. A gap in the literature around capacity building models for knowledge mobilisation led the authors to explore Developmental Evaluation as a potential approach. Naturally occurring evidence was used to develop Evidence for Change. Questionnaires, focus groups and structured interviews were used to assess the impact. Results demonstrated that Evidence for Change supported evidence-informed practice change and learning for individuals, teams, organisations and local communities. The report concludes that embedding Developmental Evaluation principles into Evidence for Change was instrumental in providing an innovative capacity building model for effective knowledge mobilisation in health and social care.